Impact of the COVID-19 pandemic on hospital-based heart failure care in New South Wales, Australia: a linked data cohort study - Daniel McIntyre; Desi Quintans; Samia Kazi; Haeri Min; Wen-Qiang He; Simone Marschner; Rohan Khera; Natasha Nassar; Clara K. Chow (BMC, 2024)
Abstract Background Healthcare policy implemented during the COVID-19 pandemic may have impacted the health of patients with heart failure. Australian data provide a unique opportunity to examine service disruption independent of significant COVID-19 burden. This study aimed to examine heart failure care during the pandemic in New South Wales (NSW). Methods Analysis of hospital utilisation among patients aged ≥ 18 years with a primary diagnosis of heart failure conducted using linked administrative health records from hospital admission, emergency department, non-admitted services, and mortality data collections. Health service utilisation and outcomes were compared "Pre-pandemic" (PP): 16th March 2018 - 28th August 2019 and "During pandemic" (DP): 16th March 2020 - 28th August 2021. Mortality data were available until December 2021. Results Heart failure-related ED presentations and hospital admissions were similar between the periods (PP = 15,324 vs DP = 15,023 ED presentations, PP = 24,072 vs DP = 23,145 hospital admissions), though rates of admission from ED were lower DP (PP = 12,783/15,324 (83.4% [95% CI 82.8-84.0]) vs DP = 12,230/15,023 (81.4% [95% CI 80.8-82.0%]). There was no difference according to age, sex, rurality, or socioeconomic status. Outpatient volume reduced DP (PP = 44,447 vs DP = 35,801 occasions of service), but telehealth visits increased nearly threefold (PP = 5,978/44,447 (13.4% [95% CI 13.1-13.8%]) vs DP = 15,901/35,801 (44.4% [95% CI 43.9-44.9%]) with highest uptake among the wealthy and those in major cities. Time to heart failure-related ED presentation, hospitalisation or all-cause mortality following index admission was longer DP (PP = 273 [IQR 259, 290] days, DP = 323 [IQR 300, 342] days, HR 0.91 [95% CI 0.88, 0.95]). Conclusions Policies implemented DP had minimal impact on volumes of inpatient heart failure care in NSW hospitals, but there were fewer admissions from ED and reduced volumes of publicly funded outpatient care. A rapid shift from patient-facing to remotely delivered care enabled compliance with restrictions and was associated with increased time to heart failure-related adverse events, but access was not afforded equally across the socio-demographic spectrum.